(untitled) (Research, Society and Development, 2020)
To describe nursing care, based on the Science of Unitary Care, which can be performed as facilitators in the process of parental adaptation in the country of premature babies hospitalized in a Neonatal Intensive Care Unit. This is a bibliographic search based on scientific articles published from 2015 to 2020, available electronically in the Virtual Health Library, in the Scientific Electronic Library Online, and in the journals portal of the Coordination for the Improvement of Level Personnel. Higher. As a result, a central category called “Nursing Care that helps in forming a bond between family and premature” was obtained, consisting of nine cares, which are related to the elements of the Clinical Caritas Veritas Process: Encourage skin to skin contact ( kangaroo); Include the family in the routine of basic care for premature babies; Provide welcome and emotional support; Encourage the approach of parents through touch and conversation with the newborn; Encourage parents to stay longer in the Neonatal Intensive Care Unit; Clarify doubts and support breastfeeding; Provide clear information with easy to understand terms; Provide guidance and continuous monitoring; Promote effective communication between the health team and the family. This study collaborates with research in the field of neonatology by reinforcing the importance of developing an authentic and genuine care relationship between health professionals, especially Nursing, and the parents of hospitalized premature newborns.